A violência e as suas variadas formas de expressão - um estudo sociocultural do filme Amarelo Manga (2003, Cláudio Assis) - Antunes, Daiane Stefane Lima (2018)
This dissertative work employs the work of filmic art at the center of the process of historical analysis, problematizing it in the dimensionality that it provides us as a social and artistic object. Therefore, the problem that permeates this work is the understanding of the Amarelo Manga film as an artistic product of a sociocultural space permeated by its own inclinations, the space and time of the cultural scene of Pernambuco in the twentieth century is the concern of the first chapter of this work, aiming to understand the space of articulation of the filmmaker of the work in question. The second concern is to aesthetically analyze the film, so we support a concept of the cinematographic area that is the process of decupage. In the third chapter we aim to observe the reception of the cinematographic critique of the film in question, since this analysis gives us indications of how such work was seized and absorbed in a time and place. Moreover, in this chapter we walk in the understanding of the social and historical dimensionalities contained in the film narrative, having as axis of observation the apprehension of reality and the latent historicity. To do so, we use a theoretical-methodological contribution that provides us grounding and strength in the notions expressed in the succeeding pages. Having in the way the reflections of Ismail Xavier, Marcel Martin, Noël Burch, Raymond Williams, Karl Marx and other theorists that were raised.